Disengaging from political activism: A critical review of the literature - Simiti, Marilena (The Greek Review of Social Research, 2024)
The literature on political disengagement has proliferated since the global upsurge of mobilizations in late 2010. Studies show that disengagement is a highly dynamic process, shaped by the interaction of a multiplicity of factors at the micro-, meso- and macro-levels. The article reviews the principal factors related to disengagement, revealing their varied impact, the significance of agential factors and the context-specific nature of disengagement. Given the different forms and degrees of disengagement, scholars have begun to challenge strictly defined dichotomies such as engagement/disengagement. The article concludes by noting some blind spots in the literature and providing suggestions for future research.